Mental set of mothers of sexually abused children: an ideal for overcoming - Carvalho, Quitéria Clarice Magalhães; Braga, Violante Augusta Batista; Galvão, Marli Teresinha Gimeniz; Cardoso, Maria Vera Lúcia Moreira Leitão (Rev Rene, 2010)
Since the 1980s, violence and crime have confusedly increased. The aim of this research was to understand maternal expectations about the future of their children victims of child sexual abuse. It is a qualitative study with the participation of ten mothers of children who are victims of sexual abuse, attended at an institution in Fortaleza, Ceará, Brazil, in 2007. Recorded interviews were used for the production of data and the discourse of collective subject was used for analysis. Then the following central ideas emerged: an overcoming future besides caring with love and money as a determining factor. The informants expressed hope that the children will fully overcome the consequences of abuse, although the degree of overcoming is related to the type of abuse and relationship of the victim with the aggressor. The resilience of the child and the feeling of motherhood feed the hope for a future free from damage caused by sexual abuse.